Detecting Predeath Grief in Family Caregivers of Persons With Dementia: Validity and Utility of the Marwit-Meuser Caregiver Grief Inventory in a Multiethnic Asian Population. (15th June 2017) - Liew, Tau Ming; Yeap, Beow Im; Koh, Gerald Choon-Huat; Gandhi, Mihir; Tan, Kheng Siew; Luo, Nan; Yap, Philip
Abstract: Background and Objectives: Coping with predeath grief (PDG) is an unmet need in caregivers of persons with dementia (PWD). The Marwit-Meuser Caregiver Grief Inventory (MM-CGI) and its abbreviated MM-CGI-Short-Form (MM-CGI-SF) are among the few empirically developed scales that detect PDG, yet they have not been substantially validated outside United States. We evaluated the reliability and validity of the PDG scales in a multiethnic Asian population distinct from that of United States. Research Design and Methods: Family caregivers of community-dwelling PWD ( n = 300) completed self-administered questionnaires containing MM-CGI and other scales of related construct. Sixty percent of the participants repeated the questionnaires 1 week later for test-retest reliability. Internal-consistency reliability was assessed by Cronbach's α, test-retest reliability by intraclass-correlation-coefficient, construct validity by Spearman's correlation-coefficient, and factorial validity by confirmatory factor analysis (CFA). Cohen's κ was used to compare the agreement between MM-CGI and a commonly-used caregiver burden scale (Zarit Burden Interview). Results: MM-CGI and MM-CGI-SF demonstrated internal-consistency reliability, test-retest reliability, construct validity, and known-group validity. In CFA, MM-CGI showed modest model-fit (comparative-fit-index, CFI = .80; Tucker-Lewis-index, TLI = .79), whereas MM-CGI-SF showed better model-fit (CFI = .91; TLI = .90). Eighty-six percent of the caregivers reported average or high levels of PDG, with 18% reporting high PDG. High scores in the caregiver burden scale only showed modest agreement with high scores in MM-CGI ( κ = .47). Discussion and Implications: MM-CGI and MM-CGI-SF demonstrated adequate psychometric properties and utility, beyond that of a caregiver burden scale, in detecting high PDG in a multiethnic Asian population. They open the way for PDG intervention in clinical care, as well as further exploration in caregiver research.